Elevational changes in insect herbivory on woody plants in six mountain ranges of temperate Eurasia: Sources of variation - Kozlov Mikhail V; Zverev Vitali; Zvereva Elena L (WILEY, 2022)
Current theory predicts that the intensity of biotic interactions, particularly herbivory, decreases with increasing latitude and elevation. However, recent studies have revealed substantial variation in both the latitudinal and elevational patterns of herbivory. This variation is often attributed to differences in study design and the type of data collected by different researchers. Here, we used a similar sampling protocol along elevational gradients in six mountain ranges, located at different latitudes within temperate Eurasia, to uncover the sources of variation in elevational patterns in insect herbivory on woody plant leaves. We discovered a considerable variation in elevational patterns among different mountain ranges; nevertheless, herbivory generally decreased with increasing elevation at both the community-wide and individual plant species levels. This decrease was mostly due to openly living defoliators, whereas no significant association was detected between herbivory and elevation among insects living within plant tissues (i.e., miners and gallers). The elevational decrease in herbivory was significant for deciduous plants but not for evergreen plants, and for tall plants but not for low-stature plants. The community-wide herbivory increased with increases in both specific leaf area and leaf size. The strength of the negative correlation between herbivory and elevation increased from lower to higher latitudes. We conclude that despite the predicted overall decrease with elevation, elevational gradients in herbivory demonstrate considerable variation, and this variation is mostly associated with herbivore feeding habits, some plant traits, and latitude of the mountain range.